SAFETY IN WORK ACTIVITIES IN POLYTECHNIC TRAINING OF PRIMARY SCHOOLS - SERAFIN, Cestmir (Trends in education, 2024)
Polytechnic education has come more to the fore in the last decade. The paper deals with the safety and health protection of pupils in the educational process at primary school in the context of the implementation of technical or polytechnic education and thus work activities in school or shared workshops. The paper maps the area of application of health and safety principles in the primary school environment during pupils' work activities, especially the issue of accidents in school workshops. The issue of accident risks related to the use of specific types of work tools is discussed with the results of a research survey among pupils in grades 6-9.
Keywords: polytechnic education; education; primary school; safety and hygiene; work activities